SNEDDS Sebagai Sistem Penghantaran Baru Berbasis Sediaan Gel Tea Tree Oil Untuk Anti Jerawat - Firdani, Alnessia; Pratiwi, Mutia Dian; Pramitasari, Kharisma; Suryani, Putri Jian; Pratiwi, Elasari Dwi (Media Farmasi, 2024)
Acne is a skin condition that is often discussed, especially among teenagers, because of its potential to damage self-confidence. The use of cosmetics that contain anti-acne active compounds from natural ingredients, such as tea tree oil, is one of the effective acne treatments. Tea tree oil is an essential oil that has hydrophobic and lipophilic properties. So, a good conveyor system such as SNEDDS is needed. The SNEDDS tea tree oil gel preparation in this study aims to assess the potential inhibition of the preparation against staphylococcus epidermidis, a type of acne-causing bacteria. The data analysis in this study uses descriptive methods, such as homogeneity test, organoleptic test, pH test, dispersion test, viscosity test, stability test, and antibacterial test. Antibacterial activity data is data obtained in the form of the diameter of the obstacle area and measured using a caliper. The results of the antibacterial activity test against staphylococcus epidermidis bacteria are as follows: positive control (Clindamycin) has an inhibition of 32.26 mm, F1 (SNEDDS tea tree oil 0% gel) does not inhibit, and F2 (SNEDDS tea tree oil 20% gel) has an inhibition of 24.44 mm. Thus, it can be concluded that SNEDDS tea tree oil gel has the ability to inhibit bacteria in the very strong category (>10mm).